High‐frequency Trading: Review of the Literature and Regulatory Initiatives around the World1. (February 2016) - Chung, Kee H.; Lee, Albert J.
Abstract: This paper provides a review of the literature on high‐frequency trading and discusses various initiatives taken by regulatory authorities around the world to address its potential detrimental effects on market quality and investor welfare. Empirical evidence to date generally suggests that high‐frequency trading has improved market quality during normal times. What is not clear is the role of high‐frequency traders during episodic periods of market crash and extreme volatility. A fruitful area of future research may be a comparative analysis of the role of high‐frequency traders and the efficacy of various regulatory initiatives across periods of varying market conditions.